La science politique est-elle une affaire politique ? - Thibaud Boncourt; Pierre-Louis Six (Revue d’Histoire des Sciences Humaines)
This article focuses on the World Congress of Political Science organised in Moscow in 1979 by the International Political Science Association (IPSA). By showing that this event is not political in essence, the article seeks to contribute to an analysis of the relationship between political science and political power in the 20th century. We start by examining the conditions of possibility of such an event, showing that the holding of the Congress, in the context of the Cold War, can be explained by the forms of politicisation and depoliticisation to which it was alternately subjected. We then analyse the congress itself and, more particularly, the mobilisation of certain Soviet scholars, who harnessed it to working towards institutionalising political science in the Union of Soviet Socialist Republics (USSR). Lastly, the article returns to the political and scientific effects of this event, and suggests that the congress helped develop the space of what could be expressed politically in the USSR, through the figure of the political scientist, which it valorises and inscribes within the world of the Soviet media. The article also insists on the fact that the event lastingly modified the practices of the IPSA and, consequently, the logics of internationalisation of the discipline.